2004
DOI: 10.1002/mrc.1468
|View full text |Cite
|
Sign up to set email alerts
|

1H, 13C and 15N NMR spectra of ciprofloxacin

Abstract: 1H NMR assignment, including the values of delta(H) and J(H,H) for the cyclopropane moiety, and 13C NMR and 15N NMR spectral data for ciprofloxacin are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…3. Obtained results are in good agreement with previously published data for these fluoroquinolones in the zwitter-ion or free base form (17,24,25).…”
Section: Computation and Data Processingsupporting
confidence: 91%
“…3. Obtained results are in good agreement with previously published data for these fluoroquinolones in the zwitter-ion or free base form (17,24,25).…”
Section: Computation and Data Processingsupporting
confidence: 91%
“…The crystal structure of ciprofloxacin alone showed that the cyclopropane ring is located almost perpendicular to the plane of the chinolon ring [16,17]. This fixed position of the cyclopropane ring could be the same in the HSA [14]. Therefore, the binding groove of HSA would fit to a band of atoms starting from H5, extending to the carboxylate and ending with H2 and one face of the cyclopropane ring (Ha/Ha ).…”
Section: Resultsmentioning
confidence: 95%
“…Because the solubility is decreased when compared to acidic conditions [11], ciprofloxacin has been typically analysed by NMR under non-physiological conditions (acidic D 2 O, DMSO [12][13][14]). As a comparison the proton chemical shifts of this study and of Sakai et al [15] are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…nm aer modication may be attributed to the formation of aggregated structures. 35 The peak at 2.8 ppm corresponds to the methylene group of GA. 25,31 To support this observation, DLS measurements on CDs and CDGAC were carried out.…”
Section: Resultsmentioning
confidence: 99%